Differences in Levels of Soluble E-selectin and VCAM-1 in Malignant versus non Malignant Mediterranean Spotted Fever - Dignat-George, Françoise; Tissot-Dupont, Hervé; Grau, Georges-Emile; Camoin-Jau, Laurence; Raoult, Didier; Sampol, José (Thrombosis and Haemostasis, 1999)
In the present study, we investigated the plasma levels of soluble adhesion molecules E-selectin, P-selectin, intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) in 24 patients with Mediterranean spotted fever (MSF), 6 of whom with a malignant form. Measurements were performed on blood samples collected before treatment (T1), then twice during treatment (T2 and T3). Before treatment, MSF patients taken as a whole presented elevated levels of sICAM-1 and sVCAM-1 and normal levels of sE-selectin and sP-selectin compared to healthy controls. We found that sICAM-1 was elevated both in mild and malignant MSF. sE-selectin and sVCAM-1 were elevated only in patients with the malignant form and allowed to discriminate the two clinical subgroups. Their levels decreased after treatment with sE-selectin reaching control values at T2 whereas sVCAM-1 remained higher over the course of the malignant form. In patients with mild MSF, sP-selectin steadily increased after treatment, whereas it did not present any modification at any of the two sampling times in patients with the malignant form. Raised plasma levels of sE-selectin and sVCAM-1 reflect endothelial activation in malignant rickettsial disease and may be sufficiently early markers to influence the therapeutic decision.
Keywords: Soluble adhesive molecules; endothelial cell; Mediterranean spotted fever